Amorphous thin films in the gallium–chalcogen system. Issue 6 (6th May 2016) - Popescu, M.; Sava, F.; Lőrinczi, A.; Velea, A.; Simandan, I. D.; Galca, A. C.; Matei, E.; Socol, G.; Gherendi, F.; Savastru, D.; Miclos, S.
Abstract : Thin amorphous films based on gallium–chalcogen (Ga–Ch), namely Ga2 S3, Ga2 Se3, Ga2 Te3, and GaTe have been prepared by pulsed laser deposition (PLD). The films were characterized by X‐ray diffraction, extended X‐ray absorption fine structure (EXAFS), energy‐dispersive X‐ray spectroscopy (EDX), optical transmission spectroscopy, ellipsometry, and electrical measurements. Structural measurements showed that Ga is threefold coordinated, except the Te‐based alloys were, it seems, only twofold coordinated, while the chalcogen is usually twofold coordinated. In all the compositions, layered and chain‐like structures are assumed. The bandgaps range between 1.09 eV for Ga2 Te3 and 2.21 eV for Ga2 Se3 .